Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Display of: 10 8x10 photos and descriptions of County Courthouses, texts on Courthouse history, plaques listing judges and Fresno County Bar Association Presidents